2013
DOI: 10.1007/s00467-012-2395-2
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative plasma FGF23 levels predict acute kidney injury in children: results of a pilot study

Abstract: FGF23 may serve as a pre-operative prognostic indicator of the development of AKI following cardiopulmonary bypass surgery in pediatric patients without CKD. Identifying patients more likely to have AKI following surgery provides a means of achieving closer clinical management of AKI and fluid balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 18 publications
3
32
2
Order By: Relevance
“…Ali et al followed a cohort of 19 pediatric patients without CKD who were scheduled to undergo cardiac surgery. [35] Of those, 5 children developed AKI post-operatively. Pre-operative FGF23 levels were higher in the patients who went on to develop AKI (median 323 vs 69 RU/mL) and peak FGF23 levels measured within 4 days post-operatively were also higher in the AKI group (median 1010 vs 196 RU/mL).…”
Section: Alterations In Fgf23 In Akimentioning
confidence: 99%
See 2 more Smart Citations
“…Ali et al followed a cohort of 19 pediatric patients without CKD who were scheduled to undergo cardiac surgery. [35] Of those, 5 children developed AKI post-operatively. Pre-operative FGF23 levels were higher in the patients who went on to develop AKI (median 323 vs 69 RU/mL) and peak FGF23 levels measured within 4 days post-operatively were also higher in the AKI group (median 1010 vs 196 RU/mL).…”
Section: Alterations In Fgf23 In Akimentioning
confidence: 99%
“…Interestingly, preoperative FGF23 levels also correlated with increased fluid gain and longer ventilation time post-operatively. [35] While the authors speculate that the elevated levels pre-operatively may indicate a derangement in renal function undetectable by conventional measures such as creatinine or cystatin C, an alternative explanation would be that the pre-operative levels reflect a poorer cardiac status in those 5 patients (who as a group had a nearly double cross-clamp time during the surgery compared with controls). Elevated FGF23 levels have been reported in pediatric patients with heart failure but without CKD and correlate with severity of heart failure and left ventricular dilation.…”
Section: Alterations In Fgf23 In Akimentioning
confidence: 99%
See 1 more Smart Citation
“…In a murine model of AKI, circulating FGF23 levels increased as early as one hour after AKI induction, and did so independently of phosphate, calcitriol, and PTH (7). Studies in humans with AKI have demonstrated that FGF23 concentrations, determined by the C-terminal assay, are increased in both adult (79) and pediatric (10) patients, and that these elevated levels are associated with poor clinical outcomes (8,9). However, it is unknown whether the high FGF23 levels in AKI reflect the intact, bioactive molecule or C-terminal fragments.…”
Section: Introductionmentioning
confidence: 99%
“…Children with CKD were excluded and both pre- and post-operative plasma samples were analyzed [33]. Patients who developed AKI following cardiac surgery had elevated FGF23 C-terminal ELISA readings both pre- and post-operatively compared with children who did not develop AKI (Table 1).…”
Section: High Circulating Fgf23 Is Associated With Higher Risk Of Akimentioning
confidence: 99%